Dampak Istri Sebagai Pencari Nafkah Utama Terhadap Penerapan Fungsi Keluarga di Kelurahan Cupak Tangah Kota Padang - Roshe, Dini; Elvawati, Elvawati; Erningsih, Erningsih (Jurnal Akuntansi Hukum dan Edukasi, 2024)
This study aims to describe the impact of wives as the main breadwinners on the implementation of family functions in Cupak Tangah Village, Padang City. The theory used in this research is structural functionalism proposed by Robert K. Merton. This research uses a qualitative research approach with a descriptive type. Selection of informants in this study is using purposive sampling technique with a total of 24 informants. The types of data used are primary data and secondary data. Data collection methods are carried out in three events, namely observation, interviews, and document studies. The unit of analysis in this research is the individual. Data analysis used with the interactive analysis model proposed by Milles and Huberman, which consists of (1) data collection (2) data reduction (3) data presentation (4) conclusion drawing. The results of this study indicate that when the wife is the breadwinner in this family, it will have an impact on family functions, which can be seen in three aspects, namely: (1) the impact on the husband consists of a) economic function: work, income / income. b) affective function: providing affection, emotional bonds (communication).  (2) the impact on children consists of a) affective function does not work: less attention given, lack of interaction with children b) educational socialization function: less time to guide learning c) recreational function: joint activities at home, activities outside the home d) educating children to be independent (3) the impact on the wife herself: domestic work becomes neglected, less time to rest.